Pengawasan Partisipatif Dalam Mencegah Pelanggaran Pemilu 2024: Studi di Bawaslu Kota Blitar - Erwin Widhiandono; Rosa Widya Ningtyas (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Indonesia, as a rule of law country, establishes the conduct of General Elections (Pemilu) based on Article 22E paragraph (1) of the 1945 Constitution of the Republic of Indonesia: "General Elections shall be conducted directly, publicly, freely, confidentially, honestly, and fairly every five years." Elections are a form of democracy that underpins the sovereignty of the people, empowering them to play a crucial role in determining the government through the voting process. To ensure honest and fair elections, electoral supervision is of paramount importance. Electoral supervisors are tasked with overseeing and safeguarding all stages of the elections, ensuring compliance with the principles of direct, public, free, confidential, honest, and fair elections. Additionally, they ensure that the electoral organizers operate independently, honestly, fairly, with legal certainty, order, transparency, proportionality, accountability, effectiveness, and efficiency. The Election Supervisory Body (Bawaslu) plays a central role in overseeing the implementation of electoral stages and handling violations that may occur. This research employs the juridical-empirical method, which examines the actual conditions. The primary data sources are direct interviews with relevant parties, while the secondary data is based on laws, regulations, and data from the Election Supervisory Body of Blitar City.The research findings reveal the efforts of Bawaslu Blitar City in realizing participatory supervision in preparation for the 2024 simultaneous elections, including: a. Participatory Supervision for First-time Voters in High Schools, b. Participatory Supervision Education for the Academic Community of Blitar City, c. Involvement of Alumni of the Participatory Supervision Training Center. Despite the significance of participatory supervision, its implementation faces various challenges, such as low public participation in election supervision, the increasing complexity of election violations, and the lack of a comprehensive supervision curriculum by Bawaslu to equip the involved community in electoral supervision.